Old Cricket - Wheeler, Lisa, 1963-; Goembel, Ponder (New York : Atheneum Books for Young Readers, 2003)
Old Cricket doesn't feel like helping his wife and neighbors to prepare for winter and so he pretends to have all sorts of ailments that require the doctor's care, but hungry Old Crow has other ideas.
"A Richard Jackson book."
Pub Weekly
School Library Journal starred
Wilson's Children
3.6
K-3
Keywords: Behavior -- Fiction; Crickets -- Fiction; Crows -- Fiction; Helpfulness -- Fiction; Crickets -- Fiction; Crows -- Fiction; Helping behavior -- Fiction; Human behavior -- Fiction